ANALISIS STRATEGI PENGEMBANGAN MINUMAN HERBAL INSTAN (STUDI KASUS : UPPKS MADYA XI KARAWANG) - Rosyda, Diana Mawar; Arman, Arman (Universitas Trilogi, 2022)
This research is a descriptive qualitative research on the analysis of the development of instant herbal beverage business at UPPKS Madya XI Karawang. The analysis method used is swot analysis method (Strength, Weakness, Opportunity, Threat) which aims to know how the strategy used by UPPKS Madya XI Karawang in its business development and QSPM which aims to establish the right alternative strategy for use by UPPKS XI Madya Karawang in better business development. The data used in this study comes from observations made directly on companies, interviews, and documentation. The results of this study were obtained from the calculation of IE matrix, IE matrix is obtained from the results of IFAS matrix with a value of 3,020 and EFAS with a value of 2,687 which based on the IE matrix of the company is in the cell or quadrant IV is a growth and development strategy consisting of intensive strategies such as the company's growth to product development in the market, market development and market penetration and integration from the front, back and horizontally. in the QSPM matrix with a TAS value of 5,329 in the first place, namely maintaining the network and expanding the connection and increasing the number of distributors. These factors become one of the alternative strategies that can be used by companies.